Physicochemical properties of binary mixtures of 1, 1, 3, 3-tetramethylguanidine imidazolide ionic liquid with water and alcohols. (June 2016) - Ye, Fangfang; Zhu, Jiahong; Yu, Keke; Zhu, Ruyu; Xu, Yingjie; Chen, Jiayi; Chen, Lingxiao
Highlights: Density and viscosity of binary mixtures of [TMG]IM with water were measured at T  = (293.15 to 313.15) K. Electrical conductivity and refractive index of binary mixtures of [TMG]IM with water and alcohols were determined. Excess properties of the mixtures were calculated and fitted to Redlich–Kister equation. Intermolecular interactions of [TMG]IM + water mixture were analyzed and compared to those of [TMG]IM + alcohol mixture. Abstract: In this work, densities and viscosities of aqueous solution of 1, 1, 3, 3-tetramethylguanidine imidazolide ([TMG]IM) ionic liquid were measured at temperatures from T  = (293.15 to 313.15) K. Volumetric properties including excess molar volumes V E, apparent molar volumes, partial molar volumes, and excess partial molar volumes were calculated from the experimental density. Viscosity deviations Δ η, Gibbs energy and excess Gibbs energy of activation for viscous flow were deduced from the viscosity. Moreover, electrical conductivities κ and refractive indices of binary mixtures of [TMG]IM with water and alcohols were determined at 298.15 K. The results show that V E values of {[TMG]IM (1) + water (2)} mixture are negative over the whole composition range, while Δ η and refractive index deviations Δ n D values exhibit positive deviations, indicating that the hydrogen bonding interaction between [TMG]IM and water is dominant. The absolute values of V E and Δ η of the mixture decrease with the increasing temperature. The V E, Δ η, and Δ n D can be fitted by the Redlich–Kister equation with satisfactory results. The concentration-dependent κ of the studied systems are fitted to Casteel–Amis equation, showing that the κ values of {[TMG]IM (1) + water (2)} mixture are much higher than those of {[TMG]IM (1) + ethanol (2)} mixture.